Ð¡Ñ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð½Ð¾-Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ Ð¾ÑÐ¾Ð±ÐµÐ½Ð½Ð¾ÑÑ‚Ð¸ Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ñ‹Ñ… Ñ€ÐµÑ†ÐµÐ¿Ñ‚Ð¾Ñ€Ð¾Ð² - Vyazovska, O. V.; Mazalov, V. K.; Kompaniets, A. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
In this review there are featured the current notions about cold receptors and presented the data about structural and functional properties of temperature transient receptor potential (TRP) channels, being the primary detectors of environmental temperature.